(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The quest for identity is a recurring theme in literature, delving into the multifaceted nature of individual selfdiscovery. This article explores the exploration of identity in Chitra Banerjee Divakaruni’s The Palace of Illusions and Anita Nair’s Ladies Coupe two novels that offer distinct perspectives on this journey. The Palace of Illusions reimagines the Mahabharata through the eyes of Draupadi, a woman struggling to establish her identity in a patriarchal society, marked by keywords such as mythology, reimagination, and patriarchy. Meanwhile, Ladies Coupe presents a contemporary narrative featuring the character Akhila, whose search for identity is characterized by empowerment, independence, and society’s expectations. These novels offer unique insights into the timeless struggle for selfhood, using diverse settings and protagonists to illustrate the complexities of identity formation and reformation. Readers are invited to contemplate the cultural, historical, and societal dimensions that shape an individual’s quest for identity.